Host traits, lifestyle and environment are associated with human skin bacteria. (18th May 2021) - Moitinho‐Silva, L.; Boraczynski, N.; Emmert, H.; Baurecht, H.; Szymczak, S.; Schulz, H.; Haller, D.; Linseisen, J.; Gieger, C.; Peters, A.; Tittmann, L.; Lieb, W.; et al.
Summary: Background: The human skin offers diverse ecosystems for microbial symbionts. However, the factors shaping skin–microbiome interactions are still insufficiently characterized. This contrasts with the broader knowledge about factors influencing gut microbiota. Objectives: We aimed to investigate major patterns of association of host traits, lifestyle and environmental factors with skin bacteria in two German populations. Methods: This is a cross‐sectional study with 647 participants from two population‐based German cohorts, PopGen ( n  = 294) and KORA FF4 ( n  = 353), totalling 1794 skin samples. The V1–V2 regions of the 16S ribosomal RNA (rRNA) gene were sequenced. Associations were tested with two bacterial levels, community (beta diversity) and 16S rRNA gene amplicon sequence variants (ASVs). Results: We validated known associations of the skin microbiota with skin microenvironment, age, body mass index and sex. These factors were associated with beta diversity and abundance of ASVs in PopGen, which was largely replicated in KORA FF4. Most intriguingly, dietary macronutrients and total dietary energy were associated with several ASVs. ASVs were also associated with smoking, alcohol consumption, skin pH, skin type, transepidermal water loss, education and several environmental exposures, including hours spent outdoors. Associated ASVs included members of the genera Propionibacterium, Corynebacterium and Staphylococcus . Conclusions: We expand the current understanding of factors associated with the skin bacterial community. We show the association of diet with skin bacteria. Finally, we hypothesize that the skin microenvironment and host physiology would shape the skin bacterial community to a greater extent compared with a single skin physiological feature, lifestyle and environmental exposure. Abstract : What is already known about this topic? The skin microbiome is essential for maintaining skin health. Skin bacteria abundances are associated with skin physiology patterns (microenvironments), host traits, such as age and sex, and domestic environmental factors, such as pets. Evaluation and translation of these associations are difficult because most studies have a limited number of candidate factors. What does this study add? We expand the current knowledge of factors associated with skin microbiota by revealing new factors associated with skin bacteria, including diet. We provide a comprehensive view of the factors associated with skin microbiota, which suggests that skin microenvironment and host physiology would shape the skin bacterial community to a greater extent compared with a single skin physiological feature, lifestyle and environmental exposure. What is the translational message? Future clinical research involving skin microbiota should acknowledge the associations found as potential confounders. Host factors (age, body mass index and sex) and skin microenvironments should be particularly considered because they were associated with skin bacteria at the community level. Linked Comment:  A.M. Schneider and A.M. Nelson. Br J Dermatol 2021; 185:481–483 .